Modified Intraperitoneal Chemotherapy Without Bevacizumab as a First-Line Therapy for Newly Diagnosed Advanced Epithelial Ovarian Cancer-Two Centers Experiences - Shen, Yuanming; Tang, Sangsang; Xu, Junfen; Xie, Xing; Chen, Zhongbo (Frontiers in Medicine, 2022)
Objectives: To evaluate whether the modified intraperitoneal plus intravenous chemotherapy regimen as a first-line therapy for advanced epithelial ovarian cancer (EOC) in China can be well tolerated or confer any potential benefit on survival. Methods: We evaluated the outcomes of women with newly diagnosed advanced-stage III~IV EOC treated with optimal cytoreductive surgery (<1 cm) and subsequent intraperitoneal plus intravenous chemotherapy or intravenous chemotherapy from January 2005 to December 2017 at two Gynecologic Oncology Centers in China. Kaplan-Meier survival analysis and Cox regression multivariate analysis models were performed to determine the toxicities and survival outcomes. Results: A total of 463 patients with stage III~IV EOC were enrolled. According to the propensity scores (1:2), 85 patients who received intraperitoneal plus intravenous chemotherapy (group A) were matched to 170 patients who received intravenous chemotherapy (group B). The median follow-up time was 41 months, ranging from 6 months to 155 months. However, there was no statistically significant difference in the median progression-free survival (PFS) (20 vs. 22 months, P = 0.351) or 3-year overall survival (OS) rate (80% vs. 78%, P =0.749) between the two groups. R0 primary cytoreductive surgery was the only factor related to PFS (P=0.028) and OS (P=0.005) by Cox regression analysis. The incidence of grade 3/4 adverse events did not significantly differ between the two groups. Conclusions: The efficacy of intraperitoneal chemotherapy mainly comes from the intraperitoneal drug dose intensity and cumulative dose. High-efficiency and low-toxicity intraperitoneal chemotherapy regimens still need to be found and validated.